Evidence for a modulation of the intraseasonal summer temperature in Eastern Patagonia by the Madden-Julian Oscillation - Jacques Coper (2015)
We describe the relationship between the intraseasonal component of surface air temperature (SAT) variability in Eastern Patagonia and the Madden-Julian Oscillation (MJO) during austral summer based on ~50 years of daily instrumental records, the Twentieth Century Reanalysis, and a century-long MJO index reconstruction. Our results show that the summer SAT variability in Patagonia is highly driven by the intraseasonal activity (~80%), especially by that associated with the MJO. The active MJO phases modulate the spatial mean intraseasonal temperature signal in Eastern Patagonia with ~1.5°C of amplitude. In most of the region, the warmest (coldest) conditions are found during active phase 8 (4). These opposite states of the temperature perturbations are related to almost inverse midlevel circulation anomalies over southern South America and the southwest Atlantic, which are part of a large-scale Rossby-like wave train of alternating circulation anomalies extended along the South Pacific. The corresponding outgoing longwave radiation anomalies suggest that these structures may be triggered by anomalous convection in the tropics. Furthermore, we show that intraseasonal heat waves in southeastern Patagonia tend to occur during active MJO phase 8. These events are also induced by a wave train pattern over the South Pacific, associated with other intraseasonal variability sources. Hence, as shown in a case study, circulation anomalies over the South Pacific triggered, in general, by tropical convection variability and, in particular, by the MJO activity may constructively interact with circulation patterns resulting from the extratropical dynamics, eventually leading to intraseasonal heat waves in southeastern Patagonia.